2015
DOI: 10.1159/000369517
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Colitis

Abstract: Microscopic colitis (MC) is the common denominator for lymphocytic and collagenous colitis (CC). It is now recognized as a relatively frequent cause of diarrhea that equals the prevalence of inflammatory bowel disease. Patients are typically middle-aged women, but disease may occur at every age. Patients with MC report watery, non-bloody diarrhea in the absence of endoscopic and radiologic abnormalities. Lymphocytic colitis is characterized by an increased number of intraepithelial lymphocytes, and CC by a thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“… 6 , 14 The pathogenesis of MC is largely unknown although it seems likely that MC is a multifactorial disease. 2 , 15 The histopathology is of crucial importance in diagnostics, and it is therefore mandatory that the criteria are reliable and reproducible.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 14 The pathogenesis of MC is largely unknown although it seems likely that MC is a multifactorial disease. 2 , 15 The histopathology is of crucial importance in diagnostics, and it is therefore mandatory that the criteria are reliable and reproducible.…”
Section: Discussionmentioning
confidence: 99%
“…This study also suggested that bismuth might be most effective in patients with milder degrees of diarrhea (Gentile et al 2015). Although based on these limited data, the use of bismuth appears to be effective and well tolerated (Bouma and Münch 2015). The use of bismuth in Western Europe is limited because it is not regularly available (Bouma and Münch 2015).…”
Section: Treatment:-mentioning
confidence: 90%
“…The etiology of MC is unknown, and studies to solve disease pathogenesis are still in their beginning (Park 2015) (Bouma and Münch 2015). The pathophysiology of MC is still unknown, but there is strong evidence that MC is frequently associated with the use of certain medications and certain systemic disorders (such as autoimmune diseases) (Storr 2013).…”
Section: Issn: 2320-5407mentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases discontinuation of the medication is the easiest; however not always sufficient solution to treat the MC. Although the primary response to budesonide is often good, with response rate of around 80% (14), relapses occur often (60-80%) when the treatment is stopped (9,18). Besides the relapses, patients in remission can still suffer from persisting symptoms such as abdominal pain, fatigue, arthralgia or myalgia several years after diagnosis (9).…”
Section: Introductionmentioning
confidence: 99%